2017
DOI: 10.5433/1679-0359.2017v38n2p551
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between soil organic matter and nematodes in sugarcane fields

Abstract: Sugarcane plays an important socio-economic role in northeastern Brazil. However, the low yield in this region is associated with several factors (e.g. frequent occurrence of plant-parasitic nematodes). In order to observe the influence of soil organic matter on the nematodes, this study aimed to characterize the spatial nematode distribution in a sugarcane field. The study was carried out in Goiana -Pernambuco State (Brazil), fifty days after sugarcane cutting (10 days after vinasse application). The sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…It is known that organic matter accumulation in soils could cause a decline in nematode diversity [90,91]. Contrarily, soil organic matter contents could be positively linked with soil nematodes [92], probably due to the presence of microbial communities (bacteria and fungi), which could significantly promote nematode occurrence and influence plant growth and development [93,94]. The carbon to nitrogen ratio C/N, which monitors the input of carbon and nitrogen in agricultural soils, was moderately linked to nematode patterns.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that organic matter accumulation in soils could cause a decline in nematode diversity [90,91]. Contrarily, soil organic matter contents could be positively linked with soil nematodes [92], probably due to the presence of microbial communities (bacteria and fungi), which could significantly promote nematode occurrence and influence plant growth and development [93,94]. The carbon to nitrogen ratio C/N, which monitors the input of carbon and nitrogen in agricultural soils, was moderately linked to nematode patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Organic matter accumulation in soils causes a significant decrease in nematode abundance [105,106]. Alternatively, soil organic matter contents were positively correlated with free-living nematodes [107], probably due to microbial community (bacteria and fungi) influence, which could increase significantly these nematode population abundances and contribute to plant growth [108,109]. The ratio C/N, which monitors the contribution of carbon and nitrogen in agricultural soils, was positively related to our identified PPNs.…”
Section: Effect Of Soil Characteristics On Ppn Abundance In Moroccan mentioning
confidence: 95%
“…The accumulation of organic matter in soils leads to a notable reduction in nematode abundance [43,44]. Alternatively, soil organic matter contents were positively correlated with free-living nematodes [45], probably due to microbial community (bacteria and fungi) influence, which could significantly increase these nematode population abundances and contribute to plant growth [46,47]. Oteifa [48] showed that the input of nitrogen to the soil had drastically decreased the population of M. incognito.…”
Section: Resultsmentioning
confidence: 99%